Temporal dynamics of runoff and soil loss on a plot scale under a coffee plantation on steep soil (Ultisol), Costa Rica - Villatoro Sánchez, Mario (2015)
Soil erosion is a serious threat for cultivated soils on steep slopes under tropical conditions. In Costa Rica, coffee plantations are widespread on such steep slopes in several basins used for hydroelectric generation, which are affected by soil erosion and sedimentation in dam reservoirs. For this study, surface runoff and soil loss rate were measured during three years on large experimental plots installed within a coffee field on a steep slope (60% average). The time interval for rainfall and runoff measurements was 5 min. A simple infiltration model presented by Diskin and Nazimov (1995) was used to estimate runoff during a rainfall event showing the relevance of initial soil water content in order to estimate runoff base on rainfall intensity variations. Three complementary embedded time scales were analyzed: annual–monthly, event and intra-event. The rainy seasons included 581 rainfall events giving a total depth of 2206, 1778 and 2220 mm in 2011, 2012 and 2013 respectively. Total runoff was 103 ± 55, 54 ± 14 and 33 ± 6.4 mm in 2011, 2012 and 2013 respectively. Annual average sediment concentration was about 1.3 ± 0.3 g l−1 with reduced temporal variations between years or rainfall events. The total soil loss was 1686 ± 784, 914 ± 306 and 575 ± 140 kg ha−1 for 2011, 2012 and 2013 respectively. Around 60% of rainfall and 90% of runoff and soil loss respectively came from the August–October period and more than half of it from October. Total rainfall event and soil water content explained most of surface runoff and soil loss dynamics at three time scales analyzed. Inherited soil water storage from previous year played an important role on the relationship between rainfall and runoff dynamics the following year. Soil and coffee coverage did not have a significant effect on runoff and soil loss variability due to permanently good soil coverage (even in the rainy season). This good coverage over the rainy season prevented crust development. The presence of old micro-terraces helped to reduce runoff and sediment loss. The Diskin and Nazimov model demonstrated that a combination of rainfall intensity and soil water content dynamics on an intra-event scale explained better the differences observed in runoff and soil loss on an inter-event scale. Runoff at intra event scale had high and low runoff moments depending on rainfall intensity and superficial soil layer water status and saturation of deeper layers under long rainfall events.